2013
DOI: 10.1007/s00296-012-2661-4
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of Henoch–Schönlein purpura: a systematic review and meta-analysis

Abstract: Henoch-Schönlein purpura (HSP) is the most common form of systemic vasculitis of unknown etiology. This study aimed at reviewing published studies investigating the association of genetic polymorphisms with HSP and its severity. We systematically reviewed all published data on genetic risk factors for HSP by searching MEDLINE. We also performed a meta-analysis of association studies of HLA-DRB1-01, 07, and 11, angiotensin I-converting enzyme (ACE) insertion/deletion (I/D) polymorphism. We identified 45 studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 34 publications
2
37
0
2
Order By: Relevance
“…It is suggested that carrying out more investigations, especially in populations with high prevalence of FMF mutations, would lead to better understanding (4). However, more efforts are necessary to identify the risky patients to implement preventive treatment (4). With regard to these observations, the present study investigated the frequency and clinical significance of MEFV mutations in HSP patients (14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that carrying out more investigations, especially in populations with high prevalence of FMF mutations, would lead to better understanding (4). However, more efforts are necessary to identify the risky patients to implement preventive treatment (4). With regard to these observations, the present study investigated the frequency and clinical significance of MEFV mutations in HSP patients (14).…”
Section: Resultsmentioning
confidence: 99%
“…HSP is normally described by deposition of immunoglobulin A within the small blood vessel wall (3) and, according to the diagnostic criteria of HSP, this disease would include nonthrombocytopenic palpable purpura and at least one of the other manifestations such as colicky abdominal pain, arthritis, and renal involvement with hematuria and proteinuria, which can progress towards renal failure (1). Although HSP is generally self-limiting and the major pathogenic cause of HSP is still unclear, it seems that inflectional, environmental, and hereditary factors could play important roles in the development and progress of the disease (4).…”
Section: Introductionmentioning
confidence: 99%
“…The association of HLA-DRB1*11 was documented with certain autoimmune, infectious and malignant conditions such as systemic sclerosis, Henoch-Schönlein purpura, Helicobacter pylori-positive idiopathic thrombocytopenic purpura, hairy cell leukaemia, cervical cancer and others. [33][34][35][36][37][38][39][40][41][42] Interestingly, in hairy cell leukaemia, anti-CD22 recombinant immunotoxin BL22-induced haemolytic uraemic syndrome (another, not ADAMTS13 deficiency-associated form of TMA) was also associated with HLA-DRB1*11. 33 The wide clinical spectrum of HLA-DRB1*11-associated conditions advocate the co-occurrence of additional provoking factors, because a unique mechanism is unlikely to drive all the above mentioned conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis is a good way to summarize the available evidence to provide a more robust result. Several previous meta-analyses 14,15 reported the association between ACE I/D gene polymorphism and HSP risk. However, the meta-analysis regarding the association between AGT M235T gene polymorphism and HSP/HSPN risk was rare.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, 70 studies were excluded according to the inclusion and exclusion criteria, five articles 4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] were included in our meta-analysis ( Figure 1). The retrieved data were recorded as follows: first author's surname, publication year, ethnicity, the number of cases and controls.…”
Section: Literature Searchmentioning
confidence: 99%